Obstetrical complications among adolescent girls at the maternity ward of Ignace Deen National Hospital - Balde, Ibrahima Sory; Diallo, Abdourahamane; Diallo, Mamadou H.; Sylla, Ibrahima; Diallo, Fatoumata B.; Barry, Mamadou S.; Diallo, Ibrahima T.; Sy, Telly (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The objective of this study was to highlight obstetrical complications that occurred among adolescent girls who delivered at the ward and to identify factors associated with the occurrence of such complications. Methods: This was a prospective study of descriptive and analytical type extending over a period of one year from September 1, 2016 to August 31, 2017 carried out at the maternity ward of Ignace Deen National Hospital at Conakry Teaching Hospital (CHU). It covered a continuous series of 1034 deliveries among adolescent girls. Results: The frequency of childbirth among adolescent girls was 16.7%. The main complications identified were dystocia, severe preeclampsia, eclampsia, retroplacental hematoma, placenta previa, uterine rupture, severe anemia, postpartum hemorrhage and puerperal endometritis. These complications occurred among adolescent girls aged 18 to 19, christian, skin and pelvic bones secondary school or university students. Factors associated with such complications were the marital status (p=0.010), the gestational age (p=0.012), the number of prenatal consultations (p=0.001), the place of prenatal consultation (p=0.001), the reason for admission (p=0.000) and the mode of admission (p=0.000). Conclusions: Childbirth among adolescent girls is frequent in this context; complications are numerous but they are preventable in the vast majority of cases.